Renewable Energy Sources and Ways of their Implementation in the Republic of Uzbekistan - Samadovich, Saidov Mashal (Research Parks Publishers, 2023)
In this scientific article, the foreign experiences of using renewable energy sources (RES) are studied and the ways of their implementation in the practice of the Republic of Uzbekistan are shown, the economic advantages of using renewable energy sources in the production of electricity and future forecast indicators are analyzed.